Measurment of gluon jet cross section in CMS detector in proton-proton collisions at √ - Atakişi, İsmail Okan (My University, 2023)
Jetler, yüksek enerjili proton-proton çarpışmalarında üretilen kuarkların ve gluonların fiziksel tezahürüdür ve LHC'de ölçülen en yaygın fizik nesneleri arasındadır ayrıca jetlerin üretimi ve karmaşık evrimi, proton parton dağılım fonksiyonları (PDF'ler), güçlü çiftlenim sabiti (αs) ve Kuantum Renk Dinamiği (KRD) kuralları tarafından yönetilir. Yine de genellikle pertürbatif QCD kullanılarak nicel olarak anlaşılabilirler ve PDF'ler ve αs'ler hakkında bilgi edinmek için kullanılabilirler. Bununla birlikte birçok fizik olayında elde edilmek istenen jetler gluonlar tarafından perdelenmektedir. Kuark ve gluon jetlerinin şekilleri ve özellikleri birbirinden farklı olduğundan dolayı CMS’de kullanılan ihtimal tabanlı ayrım (likelihood based discriminant QGL) metodu ile jetlerin kökenine ilişkin istatistik dahilinde bir bilgi edinmek mümkündür. Bu analiz kapsamında, CMS'de Run2 (2016) boyunca 13 TeV enerjide toplam ışınlılık değeri 36.3 fb-1 olan veriler kullanılarak anti-kT algoritması ile kümelendirilmiş R=0.4 koni yarıçaplı jetler için ölçümler yapılmıştır. Sonrasında QGL metodu kullanılarak olay üreteçlerinin içindeki özlük bilgileri yardımıyla kuark ve gluon kaynaklı jetler ayırt edilip ölçüm verilerini olay üreteçleri seviyesine taşıyarak istatistik hata payları dahilinde kapsamlı gluon jet tesir kesiti ölçümü yapılmıştır.

Jets are the physical manifestation of quarks and gluons produced in high-energy protonproton collisions and are among the most common physics objects measured at the LHC, as well as the generation and complex evolution of jets, proton parton distribution functions (PDFs), strong coupling constant (αs), and Quantum Chromodynamics (QCD). It is governed by rules. However, they can usually be understood quantitatively using perturbative QCD and can be used to learn about PDFs and αs. However, the jets desired to be obtained in many physical events are screened by gluons. Since the shapes and properties of quark and gluon jets are different from each other, it is possible to obtain statistical information on the origin of jets with the likelihood-based discriminant QuarkGluon Likelihood (QGL) method used in CMS. Within the scope of this analysis, inclusive jet measurements were carried out for R=0.4 cone radius jets with the anti-kT algorithm using the data with an integrated luminosity of 36.3 fb-1 at 13 TeV energy during Run2 (2016) in CMS. Afterward, using the QGL method, quark gluon-sourced jets were distinguished with the help of the intrinsic information in the event generators, and the measurement data was carried out to the level of the event generators. Then, a comprehensive gluon jet cross-section measurement was made within the statistical error margins.
TeV
Keywords: 13 TeV; CMS; cross section; Fizik; gluon; jet; KRD LHC; kuark; LHC; Physics; QGL; quark; tesir kesiti